The Integrity of Educational Work in Uzbekistan and Interrelationship - Shuhrat kizi, Rahmonova Sanoat (International Journal on Integrated Education, 2023)
Family is the main link of society. A stable environment in the family determines the maturity of the child and who he will be in the future. The family is a place of values and the role of education and training in human life is absolutely great. It is not for nothing that the idea that education cannot be separated from education and education from education has been put forward.